Pengaruh Model Problem Based Learning Terhadap Peningkatan Kemampuan Kognitif Siswa dalam Memahami Konsep Dasar Ilmu Ekonomi - Yogi Aditia; Ria Herdhiana; Bella Anantha Sritumini (Jurnal Pendidikan dan Pembelajaran Ekonomi Akuntansi, 2017)
This study was conducted to determine the effect of using a model of learning that is model problem based learning (PBL) on improving students' cognitive ability in understanding the basic concepts of economics, with the purpose of using PBL model can be one of effective learning model alternatives and can affect the improvement of ability cognitive students, the reason for the implementation of research is to test the theory that the model can cultivate the cultivation of students' cognitive abilities and creativity both individually and in groups. This research uses quantitative approach with quasy experiment / quasi experimental method with non equivalent control group design design, Experiment class group that is class X IPS 2 and control class group that is class X IPS 1 with population of student of class X IPS SMA Negeri 21 Bandung. The results of this study indicate that the use of PBL model can improve the cognitive ability of the experimental class students compared with the control class using the learning method commonly used by teachers, as well as the PBL model has an effect on the improvement of cognitive ability compared to the method of learning commonly used by teachers. This can be seen from the average value of experiment class is higher than the control class. It is recommended that the PBL model should be applied by the teacher in an effort to improve students' cognitive abilities on economic subjects.